Growth of 'Long Tail' in Australian journalism supports new engaging approach to audiences. Issue 1 (2nd January 2016) - Cokley, John; Gilbert, Lucy; Jovic, Lily; Hanrick, Phillipa
Abstract : An Australia-wide study of journalism employment in Australia conducted in 2007 is replicated using 2013 data and the comparative results are problematized. Three questions emerge from this process: 'What do the new data suggest for journalism employment in Australia?' 'What do they suggest for journalism practice in Australia?' and 'What do they suggest for journalism education in Australia?' Contemporary theory from outside journalism is deployed, namely that of citizen engagement. The study finds there are more jobs for journalists across more publications in Australia in 2013 than in 2007. Several drivers of the changes in the Australian journalism employment market are suggested including the strengthening demand for greater choice among media consumers. Links are also suggested between the concepts of 'choice', 'engagement' and 'financial viability'. Results suggest that journalists and publishers wishing to enhance their readers' levels of choice and engagement should moderate or decrease their traditional focus on 'information' and instead increase readers' ability and inclination to share their online content on social media. The article concludes that 'Sharing Studies' should be introduced into Australian journalism curricula.